Physicochemical Study of 'Dolomitic' Sorbents Prepared under Different Thermal Conditions. Part I. The Influence of Temperature - Elzbieta Stefaniak; Bogdan Biliński; Piotr Staszczuk (Adsorption Science & Technology)
The partial decomposition of dolomite performed within the temperature range 800-1000°C provides new sorbents, the so-called 'dolomitic' sorbents, composed of calcite and magnesium oxide. Their surface properties, such as their porosity and adsorption capabilities towards hydrocarbons, are discussed. The 'dolomitic' sorbents show a much higher specific surface area and pore volume when compared to the raw dolomite; moreover, their porous structure depends on the temperature of heating. The adsorption of selected hydrocarbons on the examined sorbents was also investigated and the adsorption energy distribution functions calculated from the adsorption data.